2006
DOI: 10.1111/j.1744-7402.2006.02071.x
|View full text |Cite
|
Sign up to set email alerts
|

Durable, Ultraluminous Structure for Incandescent, High‐Power White‐LED

Abstract: A new particle‐ and resin‐free system composed of transparent, binary single crystals entangled with each other continuously has been successfully developed for a light source for illumination. These single crystals exist in a semi‐coherent state like a block copolymer; one of these single crystals exhibits effective photoluminescence and the other plays an important role as a light guide of excitation and emitting lights. This material can have low backscattering and high quantum efficiency, resulting in twic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…The microstructure of Ce-doped MGC is lamellar, with a three-dimensional and complexly entangled configuration similar to that observed in the MGC reported in Ref. [6]. It was also found by X-ray diffraction analysis that Ce-doped MGC is composed of an Al 2 O 3 single-crystal phase and a YAG single-crystal phase, as shown in Fig.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The microstructure of Ce-doped MGC is lamellar, with a three-dimensional and complexly entangled configuration similar to that observed in the MGC reported in Ref. [6]. It was also found by X-ray diffraction analysis that Ce-doped MGC is composed of an Al 2 O 3 single-crystal phase and a YAG single-crystal phase, as shown in Fig.…”
Section: Resultssupporting
confidence: 58%
“…We used the Mo crucible that was used in the previous reports [6] and an Ir crucible with the largest linear thermal expansion coefficient of the four listed refractory metals [14,15]. By comparing crucibles made of materials with strikingly different thermal expansion, we intended to quantitatively examine the differences produced by differing thermal constriction between the inside of the crucible and the surface of the Ce-doped MGC ingot grown therein during its cooling to room temperature from melting point.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that Ce-doped MGC ingots grown in Mo crucibles could be released easily and nondestructively. The stereographic projections in the grown MGC evaluated were [11][12][13][14][15][16][17][18][19][20] [7,9]. The crystallinity of Ce-doped MGCs probably affects to optical properties for the conversion material.…”
Section: Introductionmentioning
confidence: 99%
“…Growth of MGCs by the vertical gradient freeze (VGF) [8], the laser-heated float zone (LHFZ) [9] and the micro-pulling-down (ȝ-PD) method [10] using the sapphire (Al 2 O 3 ) seed have been also reported. In the VGF method [8], seeds of the MGC, [111] YAG, a-axis [11][12][13][14][15][16][17][18][19][20] Recently, an Al 2 O 3 /YAG:Ce melt growth composite (Ce-doped MGC) has been developed to yield blue-to-yellow light conversion materials for white light emitting diodes (LEDs) with high power, low power consumption and high durability [11][12][13][14]. The growth of Ce-doped MGCs by the unidirectional solidification [11,12] and the Czochralski (Cz) method [13] have been reported.…”
Section: Introductionmentioning
confidence: 99%